Editorial: Bacteriocins and other ribosomally synthesised and post-translationally modified peptides (RiPPs) as modulators of the microbiome - Mathur, Harsh; Field, Des; Guinane, Caitriona; Begley, Maire; Upton, Mathew; Mantovani, Hilario C.; Cotter, Paul D. (Frontiers in Microbiology, 2024)
This Research Topic (RT) entitled ‘Bacteriocins and Ribosomally Synthesised Post-Translationally modified Peptides (RiPPs) as modulators of the microbiome’ focussed on various aspects of these peptides. It includes seven research articles that cover a variety of related areas, including the testing the impact of a range of bacteriocins on a simplified human intestinal microbiota, the investigation of a regulator involved in bacteriocin production, elucidation of the mechanism of action of a lantibiotic, optimisation of the heterologous production of circular bacteriocins and utilisation of in silico tools to identify novel bacteriocins, amongst other topics. The RT also includes a timely review article relating to the use of bacteriocin like inhibitory substances (BLIS) to strategically shape the oral microbiota. Here we briefly describe these studies and the insights they provide with respect to the ability of RiPPs to modulate microbiomes.